CORRELATION OF THE STATE OF CRUSTAL STRESSES, SEISMICITY AND LANDSLIDE ACTIVITY (FERGANA BASIN, TIEN SHAN) - Kalmet'eva Z.A.; Moldobekov B.D.; Abdybachaev U.A. (Федеральное государственное бюджетное учреждение науки Институт земной коры Сибирского отделения Российской академии наук, 2019)
The impacts of seismicity on the landslide activity in Kyrgyzstan have been in the focus of our study since 2010 [Kalmetyeva et al., 2010]. As the study progressed [Kalmetyeva, Moldobekov, 2012, 2013; Kalmetyeva et al., 2013, 2014], the initial problem statement has been revised as follows: do earthquake influence the occurrence of landslides, and, if so, what is the mechanism of this influence. This paper presents the results of detailed analysis of the distribution of earthquakes and landslides in space and time in correlation with focal mechanisms (azimuth and plunge of the principal compression stress axis) of earthquakes occurred in the Fergana basin and its mountainous frame. These are grounds to conclude that the landslide activity is mainly influenced by the response of the internal structure of the upper crust to local stresses. The mechanism of influence of strong earthquakes on the landslide activity is redistribution of local stresses, which results from partial release of regional stresses due to rupturing in the source zones of strong earthquakes. Using this concept of the landslide activity, a methodology of landslide-hazard mapping is the goal of our future studies aimed at the following: (1) zoning of the study area with respect to the features of the internal structure of the upper crust, (2) geological, geophysical and seismological studies of the state of stresses in the study area, (3) instrumental monitoring of landslides movements in the zones that differ in the structure of the upper crust, and (4) analysis of preparation and consequences of past strong earthquakes that took place in the study area in comparison with the landslide activity.
Keywords: SEISMIC CYCLE; EARTHQUAKE; FOCAL MECHANISM; MAIN STRESS AXES; LANDSLIDE; ATMOSPHERIC PRECIPITATION; СЕЙСМИЧЕСКИЙ ЦИКЛ; ЗЕМЛЕТРЯСЕНИЕ; МЕХАНИЗМ ОЧАГА ЗЕМЛЕТРЯСЕНИЯ; ГЛАВНЫЕ ОСИ НАПРЯЖЕНИЙ; ОПОЛЗЕНЬ; АТМОСФЕРНЫЕ ОСАДКИ